Corrosion resistance of amorphous carbon film in 3.5 wt% NaCl solution for marine application. (20th June 2020) - Wei, Jing; Guo, Peng; Liu, Linlin; Li, Hanchao; Li, Hao; Wang, Shuyuan; Ke, Peiling; Saito, Hidetoshi; Wang, Aiying
Abstract: In this work, we fabricated the tetrahedral amorphous carbon (ta-C) films with thicknesses of 20 nm, 40 nm and hydrogenated diamond-like carbon (DLC:H) film with thickness of 1.1 μm on 316 stainless steel substrate (316SS). The electrochemical corrosion performances of two typical amorphous carbon (a-C) films in 3.5 wt% NaCl solution were focused. Results revealed that both ultrathin ta-C films exhibited superior corrosion resistance than that of DLC:H film, because the high content of sp 3 bonded carbon and low porosity in ta-C films significantly suppressed the diffusion of corrosion media. However, a thickness threshold beyond 20 nm was proposed to obtain the superior corrosion resistance for ta-C films due to the emerged pitting of 316SS. For DLC:H film, the deterioration of corrosion resistance could be attributed to the hydrogen-containing interface, the large sp 2 clusters with high electron transport, and the higher porosity density in carbon matrix. Graphical abstract: Image 1 Highlights: The effects of thickness, atomic bonds and porosity on corrosion of a-C were studied. SVET revealed the distinct changes in local electrochemical performances for films. Thick DLC:H exhibited limited corrosion protective efficiency. Ultrathin ta-C with high sp 3 content and low porosity remarkably reduced corrosion.